A Marked Decrease in Speech Intelligibility Is No Longer a Major Characteristic of Vestibular Schwannoma in the Current Era - Masafumi Ueno; Makoto Hosoya; Hirotaka So; Nobuyoshi Tsuzuki; Marie N Shimanuki; Takanori Nishiyama; Hiroyuki Ozawa; Naoki Oishi (Clinical and Experimental Otorhinolaryngology, 2026)
Objectives. Speech intelligibility is reported to be markedly decreased in patients with vestibular schwannoma (VS); however, the relationship between speech intelligibility and hearing level remains poorly characterized.Methods. We created scatter plots of pure-tone audiometry (PTA) thresholds and speech discrimination scores for 473 patients with sporadic, unilateral VS. Simple regression analysis and Pearson correlation coefficients were calculated and compared with data from 173 patients with asymmetric cochlear hearing loss, including the proportion of patients with unserviceable speech intelligibility.Results. In VS patients, speech discrimination score and PTA threshold showed a strong correlation on the affected side, regardless of Koos grade or audiogram shape. The distribution was largely similar to that in asymmetric cochlear hearing loss. Although the proportion of patients with unserviceable speech discrimination was higher for VS than for asymmetric cochlear hearing loss across all hearing levels, the difference was statistically significant only in severe hearing loss.Conclusion. When adjusted for hearing level, markedly decreased speech discrimination is no longer a characteristic feature of VS.